The Nature of the curriculum for the eighties and onwards : report on a workshop held at the Reinhardswaldschule (Kassel, Germany, June 29-July 4, 1970) - Centre for Educational Research and Innovation ([Paris] : Organisation for Economic Co-operation and Development, 1972)
This document is based on the results of a workshop held at the Reinhardswaldschule, Kassel, Germany in 1970; the workshop was attended by 52 participants from 14 countries who discussed "The Curriculum from the Eighties and Onwards." A framing principle for this report is that in place of the American emphasis on method in teacher education, teaching/learning systems should be seen as a whole--as a combination of teacher, methods, substance, and materials. The report is divided into six chapters on the following topics: factors to be taken into account in constructing a curriculum for the 1980s; the implications of changes in subject fields (specific fields that are discussed include mathematics, science, native language, foreign language, humanities and social studies, and physical education and expressive arts); the implications of new teaching/learning methods and the systematic approach to change; implications of curriculum change for the school and the community; and the problem of evaluation. The report concludes that framing a curriculum for the 1980s cannot begin until consideration has been given to changes in society that are likely to influence schools. (JA)
Availability: OECD, Publications Office, 2 rue Andre-Pascal, 75 Paris 16e (No. 29.553 1972 $2.00).
At head of title: Centre for Educational Research and innovation.
Microfiche.
Keywords: Curriculum planning -- Congresses